2023
DOI: 10.1017/s0950268823000559
|View full text |Cite
|
Sign up to set email alerts
|

Role of latent tuberculosis infection on elevated risk of cardiovascular disease: a population-based cohort study of immigrants in British Columbia, Canada, 1985–2019

Abstract: We investigated the risk of cardiovascular disease (CVD) associated with latent tuberculosis infection (LTBI) (Aim 1) and LTBI therapy (Aim 2) in British Columbia, where tuberculosis (TB) incidence is low, and 86% of people with TB are born outside of Canada. Using linked immigration, public health surveillance, and health administrative databases, we developed a population-based retrospective cohort of immigrants between 1985 and 2019. A total of 49,197 participants had valid LTBI test results. Cox proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous studies have consistently shown a high risk of CVD development in TB survivors [4,9,19,20]. As an example, a meta-analysis conducted in Taiwan showed that patients with TB had a 1.76-fold increased risk of developing coronary heart disease compared to controls [19].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have consistently shown a high risk of CVD development in TB survivors [4,9,19,20]. As an example, a meta-analysis conducted in Taiwan showed that patients with TB had a 1.76-fold increased risk of developing coronary heart disease compared to controls [19].…”
Section: Discussionmentioning
confidence: 98%